PKM : Monitoring Dan Evaluasi Data Jemaat Gereja Batak Karo Protestan (GBKP) Pada Sistem Informasi Anggota Jemaat (SIAJ) Klasis Sinabun Kabanjahe: PKM : Monitoring Dan Evaluasi Data Jemaat Gereja Batak Karo Protestan (GBKP) Pada Sistem Informasi Anggota Jemaat (SIAJ) Klasis Sinabun Kabanjahe - Matondang, Zekson Arizona; Silitonga, Parasian DP; Jaya, Berkat Iman; Tondang, Artur Marcel; Samosir, Alfredo (ULEAD : Jurnal E-Pengabdian, 2023)
The GBKP Congregational Member Information System which can be accessed via the http://siaj.gbkp.or.id/ page is an application built specifically to record members of the Batak Christian Protestant Church (GBKP) congregation throughout Indonesia and all GBKP congregations in the world, the application was built to find out active church members, elderly church members, mamre church members, moria church members, gem church members, also records congregations who were born and who have passed away,The highest leadership in the Batak Karo Protestant Church (GBKP), namely the moderator, is collaborating with Santo Thomas Catholic University through the Faculty of Computer Science (FIKOM) to develop applications for congregational data collection, and inputting congregational data into the congregation's member information system.With the cooperation that goes well between the management and the Faculty of Computer Science, it is also an arena for lecturers in the Faculty of Computer Science to carry out Community Service (PKM) as a form of higher education tridharma by involving students who go to the field (Society Layer) to carry out socialization of inputting church data into the congregation member information system (SIAJ) online both through the smartphone of each congregation as well as via computers and laptops. In community service carried out by lecturers involving students which was held at the Runggun Tiganderket Sinabun Class